Defining "Talent": Insights from Management and Migration Literatures for Policy Design. Issue 3 (24th October 2018) - Cerna, Lucie; Chou, Meng‐Hsuan
Abstract : Taking the case of defining "talent, " a term that has been widely used but its definitions differ by discipline, organization, policy sector, as well as over time, we demonstrate how the basic definition of a policy subject may affect policy design and the assessment of policy outcomes. We review how "talent" is defined in two sets of literature, talent management and migration studies, and find that definitions fall under one of two categories: binary ("talent" as qualities) or composite ("talent" as a relational concept). The implications of our findings are epistemological and ontological; the findings point to diverse epistemological effects of definitions through developments of indicators, as expected, and they also reveal the policy designers' ontological starting points. Ontological perspectives are significant because they ultimately determine whether the policy assessments carried out differ in degrees or in kind. In the case of defining "talent, " this means determining which objectives the designers would set (e.g., recruiting vs. cultivating vs. introducing competition), the policy instrumentation for achieving the goals (migration measures vs. education vs. lifelong learning vs. human resource policy), and the type of assessment for measuring policy outcomes (single vs. multiple indicators, qualitative vs. quantitative). Abstract : "人才"是一个被广泛使用的术语，但其定义会因学科、组织、政策部门以及时间而发生变化，我们以定义"人才"为例，论证了政策主体的基本定义如何影响政策设计，以及对政策成果的评估。我们检阅了"人才"在人才管理和移民研究这两组文献中的定义，之后我们发现，其定义可以归属于二元（将"人才"作为品质而言）或复合（将"人才"作为关系概念而言）这两类之一 。我们的研究结果对认识论和本体论有启示意义；结果指出，如人们的预期一样，通过发展不同指标，定义便具有了多种认识论效应；但同时，我们的结果还揭示了政策设计者的本体论起始点。本体论观点很重要，因为本体最终决定了政策评估的程度或类型是否不同。在上述"人才"的案例中，定义"人才"就意味着确定政策设计者将设定哪些目标（例如，招聘、培养还是引入竞争）、实现目标的政策工具是什么（迁移措施、教育、终身学习还是人力资源政策），以及对政策结果的衡量评估方式是什么（单一还是多重指标，定性还是定量）。